Assessing the infestation-induced response on the plant host by the Indian lac insect - Shyam, Praveen; Mansoori, Adil; Raikwar, Atul; Kaushik, Sandeep; Shweta, S; Kumar, Anirudh; Lakhanpaul, Suman (Plant Science Today, 2024)
Lac, the only natural resin of animal origin is produced by the Indian lac insect- Kerria lacca. It is the by-product of the complex natural interaction between the lac insect and its host plant. Despite several studies on the perspectives of the chemistry of lac and its production, very little work has been carried out to understand the biology of lac and its associated plant taxa. The present work has been designed to understand the preliminary response if any, of the host plant against lac insect infestation. Structural studies and metabolic profiling such as the determination of total phenolics, flavonoids, antioxidants, FTIR, and GC-MS were carried out. The anatomical investigations revealed coagulation/deposition of metabolites in the infested sites. The infested bark showed higher phenolic, flavonoid content, and antioxidant activity in comparison to non-infested bark which was corroborated by Fourier-transform infrared spectroscopy (FTIR) and GC-MS biochemical analysis. This preliminary study will shed some light on understanding the lac plant host's physiological response and the putative mechanism used by the lac insect in overcoming the plant response.